Faktor-faktor Yang Mempengaruhi Implementasi Kebijakan Program Pencegahan Pemberantasan Dan Penyalahgunaan Peredaran Gelap Narkoba (P4GN) - M Junaidi; L.Hendra Maniza; Baiq Selasmiati (Universitas Muhammadiyah Mataram, 2018)
This study has the background that the eradication and abuse of drug trafficking must be handled seriously by the government. In this study, researchers wanted to know what factors influence the prevention of eradication and abuse of drugs (P4GN) programs. This study is a qualitative descriptive study with data sources used, namely primary data and secondary data and this research was conducted using Interview and documentation methods, data analysis methods used include data reduction, Data Presentation and Interesting Conclusions. The results of the study found that the issue of communication aspects here is a very important process to determine the objectives of a policy, so far the dissemination of eradication and misuse of drug trafficking (P4GN) programs has been carried out in several districts and cities in NTB, the implementation of the P4GN program can provide an explanation to the public about what drugs are and the dangers of drugs for the life of the nation and state, the issue of the P4GN program shows the attitude and responsibility of the implementors to carry out their duties properly. Regarding the disposition aspect, the character problem or the implementor's attitude in implementing implementation is a matter that influences communication and bureaucratic structures and resources involved in the implementation of the eradication and misuse of drug trafficking (P4GN) program, the attitude and responsibility of the implementers here is sufficient well.